Too late to die young [videorecording (DVD)] - Sotomayor, Dominga, 1985-; Hernández, Demian; Machado, Antar; Totoro, Magdalena (Kim Stim, 2019)
Chile 1990, at the end of Pinochet's dictatorship, a group of adolescents living in a commune, attempt to make sense of their own burgeoning desires and tangled relationships while the adults prepare for the first New Year's Eve under the promise of democracy.